Epigenetic inactivation of the p53-induced long noncoding RNA TP53 target 1 in human cancer - Díaz-Lagares, Ángel; Crujeiras, Ana B.; Lopez-Serra, Paula; Soler, Marta; Setien, Fernando; Goyal, Ashish; Sandoval, Juan; Hashimoto, Yutaka; Martinez-Cardús, Anna; Gomez, Antonio; Heyn, Holger; Moutinho, Catia; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Long noncoding RNAs (lncRNAs) are important regulators of cellular homeostasis. However, their contribution to the cancer phenotype still needs to be established. Herein, we have identified a p53-induced lncRNA, TP53TG1, that undergoes cancer-specific promoter hypermethylation-associated silencing. In vitro and in vivo assays identify a tumor-suppressor activity for TP53TG1 and a role in the p53 response to DNA damage. Importantly, we show that TP53TG1 binds to the multifaceted DNA/RNA binding protein YBX1 to prevent its nuclear localization and thus the YBX1-mediated activation of oncogenes. TP53TG1 epigenetic inactivation in cancer cells releases the transcriptional repression of YBX1-targeted growth-promoting genes and creates a chemoresistant tumor. TP53TG1 hypermethylation in primary tumors is shown to be associated with poor outcome. The epigenetic loss of TP53TG1 therefore represents an altered event in an lncRNA that is linked to classical tumoral pathways, such as p53 signaling, but is also connected to regulatory networks of the cancer cell.
Gesehen am 08.05.2020